Complexity Matching: Restoring the Complexity of Locomotion in Older People Through Arm-in-Arm Walking - Almurad, Zainy M. H.; Roume, Clément; Blain, Hubert; Delignières, Didier (Frontiers in Physiology, 2018)
The complexity matching effect refers to a maximization of information exchange, when interacting systems share similar complexities. A working conjecture states that interacting systems tend to match their complexities in order to enhance their synchronization. This effect has been observed in a number of synchronization experiments, and interpreted as a transfer of multifractality between systems. Finally, it has been shown that when two systems of different complexity levels interact, this transfer of multifractality operates from the most complex system to the less complex, yielding an increase of complexity in the latter. This theoretical framework inspired the present experiment that tested the possible restoration of complexity in older people. In young and healthy participants, walking is known to present 1/f fluctuations, reflecting the complexity of the locomotion system, providing walkers with both stability and adaptability. In contrast walking tends to present a more disordered dynamics in older people, and this whitening was shown to correlate with fall propensity. We hypothesized that if an aged participant walked in close synchrony with a young companion, the complexity matching effect should result in the restoration of complexity in the former. Older participants were involved in a prolonged training program of synchronized walking, with a young experimenter. Synchronization within the dyads was dominated by complexity matching. We observed a restoration of complexity in participants after three weeks, and this effect was persistent two weeks after the end of the training session. This work presents the first demonstration of a restoration of complexity in deficient systems.